Конституційно-правова характеристика актів місцевих органів виконавчої влади - Кравчук, Володимир Миколайович; Kravchuk, V. (Львівський національний університет ім. І. Франка, 2001)
The Constitution of Ukraine fixed up the division of state power into three branches: the legislative, the executive and the judicial one. On the local level the executive power is exercised by the local state administration. To fulfill Ukraine’s Constitution, laws of Ukraine, the acts of Ukraine’s President and government the head of the local state administration issues orders, the head of the department – instructions.
The constitution-law characteristics of the acts of the local bodies of the executive power
Keywords: законодавча, виконавча і судова влада; місцеві державні адміністрації; the legislative, the executive and the judicial branches; the local state administration; order; instruction